Latin America’s infrastructure investment situation and challenges - Lardé, Jeannette (ECLAC, 2016)
This bulletin aims to describe the situation of public and private investment in Latin America’s economic infrastructure in recent years (2008-2013), explain some of the challenges and briefly discuss the implications of investment patterns over this period.